La gestión en la recaudación de los tributos y su incidencia en el presupuesto del Gobierno Autónomo Descentralizado del Cantón Latacunga en el periodo 2016-2017 - Balseca Muñoz, Diana Lizbeth (2019)
This research project is focused on determining the incidence at municipal taxes management collection of Latacunga Autonomous Decentralized Government during 2016-2017 on General Budget. The municipal taxes collection are paid by citizens through taxes, fees, and special contributions and improvement; for this reason, theoretical bases are conceptualized, instruments are chosen and applied to determine the study ease. The methodology used is the analytical method, an interview was applied as a research technique to the GAD officials of Latacunga canton, with the valuable and necessary information to develop the study of the investigative work. In addition, a horizontal and vertical analysis was carried out, which allowed to know the percentage of participation that each one of the taxes, rates, and contributions has within the received income by the municipal GAD administration of Latacunga city, allowing determine budgeted collection compliance. A correlational analysis was also carried out taking as reference the periods 2015, 2016, 2017, 2018 and 2019. Likewise, this study shows management indicators, which allowed to evaluate the level of management effectiveness, on tributes collection. Based on these findings, it was possible to determine that the Latacunga municipal GAD has a good collection management, since the majority of taxes it is possible to raise more than budgeted, resulting in administrative efficiency, in the rates and special contributions of improvements in 2017, a higher percentage was obtained in 2016, which tells that in 2017 the collection management was improved. In addition, to perform correlational analysis, we show as a result a high positive correlation since the obtained percentages in 2015, 2016, 2017, 2018 and 2019 are close to 1, which means that they are rising significantly, therefore, the budgeted and collected values are similar.